Response surface optimization and social impact evaluation of Houttuynia cordata Thunb solar drying technology for community enterprise in Chiangrai, Thailand - Torpong Kreetachat; Saksit Imman; Kowit Suwannahong; Surachai Wongcharee; Nopparat Suriyachai (International Journal of Renewable Energy Development, 2023)
Drying has emerged as one of the most important ways of preserving high-quality and quantity food goods. A force convection solar drying is considered an ecologically and environmentally friendly alternative. This research presents parameter optimization of greenhouse tunnel dryer  of  Houttuynia cordata Thunb (H. cordata) using response surface methodology with the assessment of economic feasibility and social return on invesment. The influence parameters of the drying process were evaluated to obtain maximum efficiency. The individual parameters were temperature (40 – 60 °C), material length (10 – 30 cm), and relative humidity (30 – 50%). The individual parameters of drying temperature showed an extreme effect on the response of moisture content and color value change, while the relative humidity had only an influence on moisture content. On the other hand, the parameter of material length was not significance in both responses. When compared to open-air drying, solar drying reduced the drying time of H. cordata by 57.14%. The payback period of the dryer was found to be 2.5 years. Furthermore, the results reveal that the social return on investment ratio in 2021 was 2.18, then increasing to 2.52 in 2022 and 2.91 in 2023. According to the findings, solar drying technology has the potential to be an adequate product quality improvement technology for H. cordata. It is a feasible drying technology in terms of economic evaluation.